Perancangan Buku Cerita Anak Guna Membantu Pemahaman Alkitab - Shirley -; Rendy Iswanto (Universitas Ciputra Surabaya, 2017)
Bible teaching ought to be taught as early as possible for Christians and Catholics. One of the media that introduce the contents of the bible to children is storybook. Religious-themed children's book can be found in book stores, but the number of books with Christian values to children is fairly little. Those books do not have a lot of variety and rarely provide a method of application of the biblical text. Though the Bible is essential in the life of the followers of Jesus Christ. The main objective of this research is to know how to teach the words of God to the children in easy and interesting way. This study uses qualitative research method, such as interviews, and literature studies. Results from the study are a book that helps children understand the Bible with additional games in the book so it can be educational as well as a form of entertainment. Product sales made through book stores and Christian book store.